2006
DOI: 10.1068/p5251
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Motion Parallax and Perspective Cues on Perceived Size and Distance

Abstract: In three experiments we examined the relative effectiveness of motion parallax and two perspective cues for the perception of size and distance. The experimental stimuli consisted of two ellipses (a standard and a comparison) and a horizontal line that indicated the horizon. The subject's task was to report the apparent size and distance of the comparison stimulus relative to the standard stimulus. Two perspective cues were given by the relative heights of the two stimuli and the absolute height of the standar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 38 publications
1
6
0
3
Order By: Relevance
“…Based on these explanations of Gibson (1950), we can account for the current result showing that height cues differ from distance cues. Many previous researchers have reported that size perception was specified by the cue that was irrelevant to distance (eg Burbeck 1987;Humphrey and Morgan 1965;Tozawa and Oyama 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Based on these explanations of Gibson (1950), we can account for the current result showing that height cues differ from distance cues. Many previous researchers have reported that size perception was specified by the cue that was irrelevant to distance (eg Burbeck 1987;Humphrey and Morgan 1965;Tozawa and Oyama 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Outra possível explicação está relacionada com a Hipótese da Invariância Tamanho-Distância (HITD), que es-tabelece que se o tamanho angular de um objeto for mantido constante, o tamanho percebido será propor-cional à distância percebida (Holway & Boring, 1941;Tozawa & Oyama, 2006). Esse efeito pode ser facilmente comprovado em uma situação em que dois objetos de mesmo tamanho são posicionados em diferentes pontos do gradiente de textura.…”
Section: Discussionunclassified
“…O julgamento de tamanho de objetos é modulado por distintas informações presentes em arranjos ópticos, tais como informações pictóricas de profundidade provenientes de gradientes de textura (Aks & Enns, 1996;Torro-Alves & Fukusima, 2007;Williams & Enns, 1996) e a linha do horizonte (Bennett & Warren, 2002;Bertamini, Yang, & Proffitt, 1998;Bingham, 1993;Dixon, Wraga, Proffitt, & Williams, 2000;Rogers, 1996;Sedgwick, 1980;Wraga, 1999). É reconhecida há décadas a importância do gradiente de textura como condição suficiente para a percepção de distância (Gibson, 1979), o que repercute sobre a percepção de tamanho, já que esta requer o conhecimento sobre a distância percebida do objeto, especialmente em condições com limitações visuais (O'Brien & Johnston, 2000;Tozawa & Oyama, 2006).…”
unclassified
“…However, Rulence-Paques and Mullet (1998) suggested that participants used the information concerning height and width of the size and then integrated these two items by additive or multiplicative operations. Therefore, the area estimated might be affected by a combination of cues taken from both the horizon line and the relative height (Tozawa & Oyama, 2006). It may be that participants need to estimate both height and width of square stimuli to judge the stimulus area, but that they need only estimate the diameter of a circle to judge its area.…”
Section: Discussionmentioning
confidence: 99%